Analysis of the Impact of Marketing Mix (4ps) on Sales Volume of Servvo’s Products in Jakarta - Arsita Wickrama (International Journal Labs, 2022)
The purpose of this research is to analyze the impact of the marketing mix (4Ps) strategy on the sales volume of Servvo’s products in Jakarta. It is useful to give an insight into how the marketing mix (4Ps) can give impact the sales volume of Servvo’s products aka the fire extinguishers. This research is quantitative research. The subject of this research is the customers of Servvo in Jakarta. To determine who will be the respondents, the researcher used a random sampling of 100 respondents. The technique of collecting data was observation and questionnaire. According to the result of the research, the t count is 0,602 with df = 1,984. Where 0,602 < 1,984 within significance value 0,549 > 0,05. Therefore, H1 is rejected and H0 is accepted. We can conclude that Marketing Mix 4Ps does the to give an impact on the sales volume of Servvo’s products in Jakarta.